Designing Adaptive Human Resource Management In Pesantren: A Critical Study of Traditional Practices - Sukarno, Sukarno; Kaito Murayama (Edukasia Islamika : Jurnal Pendidikan Islam, 2025)
Pondok Pesantren is one of the oldest educational institutions in the archipelago that has an important role in building the nation's character. Although boarding schools have a strategic role in building the nation's character, many of them do not have a structured and adaptive human resource management (HRM) system, thus facing obstacles in maintaining the quality of education and the sustainability of the institution. This study aims to analyze the implementation of human resource management (HRM) at the Hasyim Asy'ari Islamic Boarding School in Tarub District, Tegal Regency, an Islamic educational institution combining religious and general education within the framework of modernization. The qualitative research method uses a case study approach through observation techniques, in-depth interviews, and documentation. The results showed that HR management in this pesantren includes several important aspects: planning, organizing, implementing, and controlling. In planning, trend analysis is used based on historical data, but it has not fully considered dynamic factors such as fluctuations in Santri enrollment. The HR organization is still limited to a formal structure, and the internal coordination system is not strengthened. Implementation stages, including recruitment, selection, orientation, training, and assessment, have been carried out but are still simple and not optimal in developing the professionalism of teaching staff. One of the main challenges is low compensation, or bisyaroh, which can affect work motivation. These findings indicate the need for a more systematic, needs-based, and oriented HRM strategy to improve the quality of teaching staff in order to produce superior Santri who are ready to face global challenges.